(untitled) (Universal International Scientific Journal, 2026)
In the 21st century, the field of education is becoming not only a means of imparting knowledge, but also a means of comprehensive development of a person, revealing his creative and intellectual potential. Achievements such as globalization, the introduction of digital technologies, artificial intelligence, robotics require flexibility from school and higher education systems. This article discusses the innovative educational environment and the spiritual development of the individual.